Percutaneous Intraarticular Peripheral Access Technique for Hip Arthroscopy - Andrew Carbone, M.D.; W. Taylor Harris, M.D.; Tyler R. McCarroll, M.D.; Allison Y. Kufta, B.S.; Elizabeth G. Walsh, B.S.; Benjamin G. Domb, M.D. (Arthroscopy Techniques)
Traditional hip arthroscopy relies on axial distraction, which is appropriate in many cases. However, it provides insufficient working area and visualization in patients with certain anatomy, risking iatrogenic damage to the labrum and femoral head and poorer outcomes. We present a technique of safer method of peripheral access of the hip joint, which reduces the of injury in patients with challenging morphology.